Assessment of the placental microbiota of preterm infants with pneumonia: a case control study - Zhang, Lei; Chen, Zijin; Hu, Shuai; Liu, Hong; Lai, Fan; Fan, Yinghong; Li, Min; Zhou, Ling (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveTo investigate the specific characteristics and differences in the placental microbiome of preterm infants with and without pneumonia.MethodsFifty-nine infants born at 32–36 weeks’ gestation were enrolled in this study. Among them, 33 developed pneumonia within 48 hours of birth, while the remaining 26 did not. Placental swabs were collected at birth for DNA extraction, from which the placental microbial composition was analyzed using a bioinformatics pipeline following PCR amplification of genetic material and subsequent sequencing of bacterial 16S rRNA.ResultsSignificant differences in both the alpha and beta diversities were found between the two groups (P<0.05). Proteobacteria, Firmicutes, and Actinobacteriota were identified as the predominant phyla in the placenta, while predominant identified genera included Brevundimonas, Caulobacter, Lactobacillus, and Citrobacter. There were no significant inter-group differences in the relative abundances of the predominant phyla and genera except Lactobacillus(P>0.05). Compared to infants without pneumonia, those with pneumonia demonstrated a decreased abundance of Lactobacillus, and an increased abundance of Ureaplasma and Staphylococcus (P<0.05). The relative abundance of Ureaplasma was positively correlated with that of Staphylococcus, and negatively correlation with that of Lactobacillus (P<0.05). Notably, we observed significant disparities in the metabolic pathways and phenotypes between the two groups (P<0.05).ConclusionOverall, this study suggests that alterations in the placental microbiome may be linked to the onset of pneumonia in preterm infants. Further investigations are required to elucidate the relationship between microbiota and disease pathogenesis.